Case Report: Novel Likely Pathogenic ACTN2 Variant Causing Heterogeneous Phenotype in a Korean Family With Left Ventricular Non-compaction - Park, Joonhong; Cho, Yong Gon; Park, Ha Wook; Cho, Jung Sun (Frontiers in Pediatrics, 2021)
Left ventricular noncompaction (LVNC) is a very rare primary cardiomyopathy with a genetic etiology, resulting from the failure of myocardial development during embryogenesis, and it carries a high risk of left ventricular dysfunction, thromboembolic phenomenon, and malignant arrhythmias. Here, we report the first case of familial LVNC in Korea, caused by a novel ACTN2 missense variant. We performed duo exome sequencing (ES) to examine the genome of the proband and his father. A 15-year-old boy was admitted for the evaluation of exertional dyspnea for 2 weeks. He was diagnosed with LVNC with a dilated cardiomyopathy phenotype (left ventricular end-diastolic dimension 60 mm, interventricular septal dimension 8.2 mm by transthoracic echocardiography (TTE)). For the screening of familial cardiomyopathy, TTE and cardiac magnetic resonance imaging (cMRI) were performed, which revealed hypertrophic and isolated LVNC in the proband’s father and sister, respectively. In particular, the cMRI revealed dense hypertrabeculation with focal aneurysmal changes in the apical septal wall in the proband’s father. ES of the father–son duo identified a novel heterozygous c.668T>C variant of the ACTN2 gene (NM_001103.3:c.668T>C, p.Leu223Pro; no rsID) as the candidate cause of autosomal dominant LVNC. Sanger sequencing confirmed this novel variant in the proband, his father, and sister, but not in the proband’s grandmother. Even within families harboring the same variant, a variable risk of adverse outcomes is common. Therefore, familial screening for patients with LVNC associated with ACTN2 variant should be performed for early detection of the LVNC phenotype associated with poor outcomes, such as dilated LVNC.